(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: In Bangladesh, when a SARS-CoV-2 infected person comes to close contact with another person, especially unvaccinated healthcare workers (HCWs) during staying at the hospital, the disease spreads among the other patients also. This study was carried out in the initial stage of the Corona virus disease 2019 (COVID-19) pandemic before the vaccination program had started. It was observed that among the HCWs some were infected by the virus while they take care of the infected patients and some suffered from subclinical infection without significant symptoms whereas some were not infected at all. Objective: To observe the seroprevalence of SARS- CoV-2 antibodies in a specific group of people (HCWs) who were healthy and unvaccinated but exposed to the patients at the COVID ward in a referral hospital. Methods: This study was carried out in Immunology and Virology Department, Armed Forces Institute of Pathology (AFIP), Dhaka Bangladesh from the date of 21st April, 2020 to 31st May, 2020. As this study was carried out in very early stage of the COVID-19 pandemic, samples were collected within a short period that is for forty days only. In this study, 294 samples were collected from apparently healthy and unvaccinated HCWs who work at the COVID wards in a referral hospital. To detect SARS-CoV-2 antibodies, Immunochromatographic (ICT) method was applied which is a well-accepted method worldwide. Results: This study revealed that among 294 samples from healthcare workers, 36% (106) cases developed antibodies but 64% (188) cases didn’t develop any type of antibody and 19.3(57) cases were PCR positive which might be possible due to their duties in COVID ward. Among 106 seroconvert cases, 16.98% (18)were positive for only IgM, 50.9% (54) were positive for only IgG and 34(32.07%)) were positive for both IgG and IgM. Among 57 infected cases, 21.05% (12) were positive for only IgM, 45.61% (26) were positive for only IgG and 33.33% (34) were for both IgG and IgM antibodies. The ratio between male and female in health-workers were 2.58:1 respectively. Conclusion: This study revealed that the serological test of SARS-CoV-2 is useful for the identification of symptomatic, asymptomatic or subclinical infection among the persons who are the close contacts of COVID-19 patients; moreover, it will help to understand the disease outbreak, the contagiousness of SARS- CoV-2 and the immunity to SARS-CoV-2 in both the vulnerable and general populations. JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 31-34